Human IgE+ B cells are derived from T cell–dependent and T cell–independent pathways - Berkowska, Magdalena A.; Heeringa, Jorn J.; Hajdarbegovic, Enes; van der Burg, Mirjam; Thio, H. Bing; van Hagen, P. Martin; Boon, Louis; Orfao, Alberto; van Dongen, Jacques J.M.; van Zelm, Menno C. (Journal of allergy and clinical immunology, 2014)
The prevalence of IgE-mediated diseases has been increasing worldwide, yet IgE-expressing B cells are poorly characterized, mainly because of their scarcity and low membrane IgE levels. We sought to study the immunobiology of human IgE-expressing B cells in healthy subjects and patients with allergic disease. We used a stepwise approach for flow cytometric detection and purification of human IgE-expressing B cells in control subjects, CD40 ligand–deficient patients, and patients with atopic dermatitis. Molecular analysis of replication histories, somatic hypermutation (SHM), and immunoglobulin class-switching was performed. Using multicolor flow cytometry, we reliably detected IgE-expressing plasma cells and 2 IgE-expressing memory B-cell subsets. These IgE-expressing cells showed molecular and phenotypic signs of antigen responses. The replication history and SHM levels of IgE+ plasma cells and CD27+IgE+ memory B cells fitted with a germinal center (GC)–dependent pathway, often through an IgG intermediate, as evidenced from Sγ remnants in Sμ-Sε switch regions. CD27−IgE+ cells showed limited proliferation and SHM and were present in CD40 ligand–deficient patients, indicating a GC-independent origin. Patients with atopic dermatitis had normal numbers of blood IgE+ plasma cells and CD27+IgE+ memory B cells but increased numbers of CD27−IgE+ memory B cells with high SHM loads compared with those seen in healthy control subjects and patients with psoriasis. We delineated GC-dependent and GC-independent IgE+ B-cell responses in healthy subjects and indicated involvement of the GC-independent pathway in a human IgE-mediated disease. These findings provide new insights into the pathogenesis of IgE-mediated diseases and might contribute to accurate monitoring of IgE+ B cells in patients with severe disease undergoing anti-IgE treatment.